The Impact of Chinese Visual Elements on Brand Recognition and Customer Loyalty in the Milk Tea Industry - Wang, Yang; Gani, Muhamad Abdul Aziz Ab; Dai, Yongli (Journal of Ecohumanism, 2025)
This article focuses on the significance of Chinese visual elements in gaining insights for brands to achieve these goals and will provide valuable insights to scholars and practitioners. The study establishes how Chinese visual elements contribute to enhancing brand identity and its recognition in both the local and global markets. The research would identify which of the visual cues are most effective in establishing a more memorable brand image. It also focuses on how Chinese aesthetics influence customer loyalty, essentially in repurchase and advocacy. The research assesses whether consumers may be more predisposed to be loyal to brands that take into consideration Chinese cultural aspects as part of their visual identity. The study also evaluates how a brand can be truly Chinese with its aesthetics while staying globally relevant. This objective will identify potential advantages or failures connected with the use of Chinese visual sensibility in branding, especially vis-à-vis a global market. The study will yield recommendations for brands on how to strike a balance between cultural authenticity and more universal consumer appeal. The findings offer insight for practitioners regarding the integration of Chinese visual elements into branding strategies, in combination with practical recommendations. Brand managers and marketers in the milk tea industry will be able to derive practical insights for creating more effective, culturally fit branding campaigns able to improve branding value and consumer loyalty. It will also cover some specifics regarding how brands can jump over the hurdles of maintaining global appeal while at the same time retaining cultural roots so that they remain fresh for assorted markets.